A aplicação do Direito Autoral no contrato inteligente - Jesus, Luanna Esselin Perdiz de (2024)
Society is constantly evolving, as is the law. Copyright law is not a recent brand for law, which has long recognized the importance of encouraging human intellectual production for the cultural, economic, and social development of a nation through the protection of the rights of intellectual property holders. However, copyright protection has recently encountered obstacles with technological advancement, the expansion of communication means, and new technologies. In order to seek ways to adapt copyright law to this modernized scenario, so that its legal relevance is preserved, this study aims to explore a promising new technology for contractual relations in the digital realm, namely the smart contract. The smart contract, in short, uses blockchain technology to automate the fulfillment of obligations and implement certain contractual conditions electronically without the presence of an intermediary. Therefore, in the search for technologies that may assist to some extent in adapting the protection of copyright law in the digital environment, the following research seeks to identify whether there is the possibility of applying copyright law to this new way of advancing contractual obligations through a smart contract. To develop the present research, the deductive method is used, and as for the procedure it is a bibliographic research, through the review of books, scientific articles, dissertations and theses; as well as documentary, due to the revision of legislative texts. It is concluded that the smart contract, in view of the scenario of constant evolution in the Digital Age, offers flexibility and greater adaptation for authors to manage their rights efficiently in the digital world, to ensure that their rights are respected and there is due remuneration, even if it is by electronic means. The application of the smart contract to Copyright lies in the ability of smart contracts to automate the immediate execution of certain contractual clauses when predefined conditions are met regarding the economic exploitation of the author's property rights in the electronic medium, which provides authors with greater management over these contracts in an ever-evolving digital world